CHARACTERIZATION OF HYDROTHERMALLY SYNTHESISED HYDROXYAPATITE BIOCERAMIC - Canbay, Canan Aksu; Mustafa, Himdad İbrahim; Özkul, İskender (My University, 2018)
In this study, hydroxyapatite (HAP) was synthesized by hydrothermal method. The structural analysis, thermal analysis and electrical characteristics of HAP sample have been investigated. The structural analysis was performed to determine the crystal structure and to observe the surface morphology of the sample. The thermal analysis was made from room temperature to 925 ?C, to determine the mass loss according to temperature and phase transitions or decomposition in the sample and also TG-DTA analysis was done to determine the thermal stability. The compositional analysis was done by EDX. I-V analysis was made to calculate the electrical conductivity value of the sample and electrical conductivity of the sample was obtained to be 1.2x10-10 S/cm.
Keywords: Mühendislik; Biyotıp; Kimya; Tıbbi; Malzeme Bilimleri; Biyomalzemeler